Assessment of power transformers using a methodology based on health indices - Núñez Mata, Óscar Fernando (2021)
The development of a proper monitoring condition of power transformers is essential for the secure and reliable operation of electric power systems. In a power transformer, the health condition is influenced by multiple factors including chemical, electrical and mechanical stresses. Therefore, it will be necessary to propose new tools to evaluate the health condition of power transformers. This paper proposes a health index (HI) to assessment the condition of power transformers. The HI is divided into two sub-indices, which determine the overall index using a series of off-line tests frequently performed. Firstly, a functional sub-index is proposed, which involves general electrical tests, such as winding resistance, transformation ratio and excitation current, as well as dissolved gas analysis. Secondly, a dielectric sub-index based on the oil tests and the power factor test. Finally, the overall HI is calculated by weighing both subindexes. The proposed methodology was evaluated using a data base containing field diagnostic tests collected from the year 2014 to 2019. The values obtained for the HI were contrasted with the records of each transformer evaluated to evaluate the effectiveness of the proposed methodology.